Analisis Karakteristik Fluida dan Temperatur Reservoir Dengan Menggunakan Diagram Ternary Cl-Li-B Pada Manifestasi Panas Bumi Di Desa Kaleosan, Minahasa Utara - Ravael Ratumbuysang; Armstrong Sompotan; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
Research on determining the fluid and temperature of the geothermal reservoir in Kaleosan village, Kalawat district, North Minahasa regency, the hot springs are 100 ml. Determination of the characteristics of geothermal fluids is carried out using the Cl-Li-B triangle diagram. The Cl-Li-B triangular diagram is used to determine the origin, boiling, and dilution of geothermal reservoir fluids. Reservoir temperature estimation is done by using silica geothermometer equation. Measurements of Li, B and Ca elements were carried out using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) and measuring SiO2 compounds using Visible Spectroscopy. Measurement of Cl elements using acid-base titration method at the PT. Indonesian WLN. Based on laboratory results and data processing and field sampling, the dominant type of chloride (Cl) concentration was obtained. The results showed that the geothermal springs in Kaleosan Village are in immature water, which indicates that the geothermal reservoir fluid has undergone dilution with other elements. The geothermal system in Kaleosan Village is dominated by water and hot springs come out in the outflow zone.